2022
DOI: 10.1063/5.0117011
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic topological defects and quantum dot assembly in a nematic liquid crystalline medium

Abstract: Liquid crystal (LC) materials exhibit interesting electro-optic switching and molecular ordering properties. Furthermore, the addition of chemically compatible active emitters such as core-shell quantum dots (QD) in a LC medium allows optical as well as dielectric tuning in an anisotropic, reconfigurable ordered medium. Order in a nematic LC phase is characterized by an orientational order parameter. In this work, we demonstrate the use of patterned substrates to generate arrays of integer topological defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The defect array formation is a result of multiple contributing factors including a difference of electric field magnitude above and below the SU-8 well walls due to dielectric shielding, field-induced drift of ionic dopant CTAB and boundary conditions imposed by the SU-8 patterns. [14] As the concentration of CTAB is increased, TD arrays (four dark brushes) become well defined and regular as seen in the 5CB LC samples doped with 0.5 wt% (Figure 2b) and 1 wt% (Figure 2c) doped CTAB. The presence of CTAB induces EHDI as the charge carriers move rapidly under the influence of the AC field and LC molecules attain poly-domain orientation as the field intensity is increased.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…The defect array formation is a result of multiple contributing factors including a difference of electric field magnitude above and below the SU-8 well walls due to dielectric shielding, field-induced drift of ionic dopant CTAB and boundary conditions imposed by the SU-8 patterns. [14] As the concentration of CTAB is increased, TD arrays (four dark brushes) become well defined and regular as seen in the 5CB LC samples doped with 0.5 wt% (Figure 2b) and 1 wt% (Figure 2c) doped CTAB. The presence of CTAB induces EHDI as the charge carriers move rapidly under the influence of the AC field and LC molecules attain poly-domain orientation as the field intensity is increased.…”
Section: Resultsmentioning
confidence: 77%
“…[24,25] Under an external electric field, the LC molecules experience a torque due to dielectric anisotropy and simultaneously the motion of free ionic species through this realigned medium can lead to a frustrated texture sustained by EHDI. [26] Previous work [14] demonstrated that the application of an oscillating electric field to 5CB-filled, CTAB-coated patterned devices leads to the formation of regular TD arrays. However, the exact role of CTAB was not clear due to its incorporation as a spincoated layer on the substrate, primarily added as an alignment layer to generate homeotropic alignment boundary conditions at the surface.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations